A scientometric study of the order Odonata with special attention to Brazil. Issue 1 (2nd January 2017) - Miguel, Thiago Barros; Calvão, Lenize Batista; Vital, Marcos Vinícius Carneiro; Juen, Leandro
Abstract : The insects of the order Odonata have an aquatic larval stage and land-dwelling adults. These insects play an important role in aquatic ecosystems and are excellent bioindicators. The present study was based on a scientometric analysis of the research available on the Odonata, which aimed to identify the principal trends and gaps in the database on these organisms, compiled online from databases of the Institute for Scientific Information – ISI, Scielo and journals Odonatologica and International Journal of Odonatology . A total of 2317 papers were analyzed, permitting the detection of the following tendencies: a gradual increase in the number of papers occurred over time, most of the papers had an ecological perspective, most focused primarily on the adult stage and species level, and 49 studies focused on bio-indication by examining variation in the composition of the community, fluctuating asymmetry, bioaccumulation, species richness and abundance, and odonate habitat index (OHI). The increase in the ecological studies of odonates may reflect the dynamic characteristics of this order, and its relatively well-defined systematics, principally in the case of the adults. Despite the increase in the number of publications, there are still many gaps, such as biogeography, parasitism, competition within and among species, evolutionary and phylogenetic relationships, as well as studies of the larval stages of these organisms. Given the sensitivity of the members of this order to environmental variables, they may be used for the evaluation of aquatic systems, given their roles as detectors, exploiters or accumulators, depending on the type of response to environmental modifications.